BIOMECHANICAL ANALYSIS OF SINGLE-LEG SQUAT WITH ISOKINETIC AND CONSTANT RESISTIVE FORCE USING CONTROLLABLE EXERCISE EQUIPMENT. Issue 4 (1st February 2017) - Kimura, Yoshinori; Koyanagi, Maki; Koyanagi, Ken'ichi; Mukai, Kouichi; Nakae, Naruhiko; Tanaka, Noriko; Sakai, Takahiro; Tada, Shuhei; Satoda, Yumiko; Kondou, Sayaka; Inoue, Akio
Abstract : Background: We have reported that a resistive single-leg squat (RSLS) exercise using exercise equipment that generates various resistance forces was effective for increasing the load on the gluteus medius and preventing knee valgus moment. However, the biomechanical characteristics of RSLS with each resistance forces have not been compared. Objective: To compare difference of the biomechanical characteristics of RSLS between isokinetic resistance force (IF) and constant resistance force (CF). Design: Quasi-experimental. Setting: Controlled laboratory setting. Participants: Six asymptomatic female college students. Interventions: Participants performed RSLS with IF and CF. A motion capture system and force plate were used for motion analysis. Surface electrodes recorded the EMG activity of the muscles of the support leg. Main Outcome Measurements: Joint moment of the support leg were calculated from 20° to 60° of knee flexion at 10° intervals. EMG data were normalized as a percentage of maximum voluntary contraction. Results: In both the tasks, external knee valgus moment was prevented. Peak internal hip abduction moment was larger in IF (2.3±0.4 Nm/kg) than in CF (1.91±0.3 Nm/kg). Internal hip abduction moment was significantly larger in CF (1.4±0.2 Nm/kg) than in IF (1.1±0.3 Nm/kg) at 20° knee flexion, but larger in IF than in CF at 50° and 60° knee flexion. No significant difference in internal hip abduction moment was found at 30° and 40° knee flexion. EMG activities were significantly larger in IF (rectus femoris, 56±16%; vastus medialis, 85±38%; gluteus medius, 85±17%) than in CF (rectus femoris, 34±10%; vastus medialis, 48±23%; gluteus medius, 59±12%). Conclusion: IF was more useful for augmenting the activity of major muscles in the support leg and internal hip abduction moment at large knee flexion angles, whereas CF was more useful for augmenting internal hip abduction moment at small knee flexion angles, where ACL injury frequently occurs.